A new strategy improving TB diagnosis: stratified urine LAM test based on lymphocyte counts - Li, Hongzhi; Gao, Xian; Liu, Dandan; Li, Zhe; Li, Jing (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundTraditional lipoarabinomannan tests have limited sensitivity in HIV-negative individuals. Our aims were to compare chemiluminescence-based LAM (AIMLAM) and other diagnostic modalities in HIV-negative patients and to explore whether lymphocyte counts impact the sensitivity and costs of AIMLAM.MethodsThis is a prospective, cross-sectional, diagnostic accuracy study. Participants underwent testing with sputum acid-fast bacilli, sputum culture, GeneXpert, and AIMLAM. Their diagnostic efficiency and cost-effectiveness alone or under different lymphocyte count categories was evaluated.ResultsUsing MRS as a reference, the sensitivities of different diagnostic methods were as follows: sputum smear 27.43%, sputum culture 45.13%, GeneXpert 74.34%, and AIMLAM 71.68%. Patients with lymphocyte counts <0.8 × 109/L were significantly more likely to have a positive AIMLAM result (OR = 9.431, 95% CI: 2.659–33.447, P = 0.001). The sensitivity of AIMLAM in patients with lymphocyte counts <0.8 × 109/L reached 93.02%. The overall cost of AIMLAM to detect a positive TB case was 129.82, lower than sputum culture (136.10) and GeneXpert (180.27). For patients with lymphocyte counts <0.8 × 109/L, the cost of AIMLAM was further reduced to 67.84 (a 47.74% decrease), which was lower than GeneXpert (111.65) and sputum culture (94.28).ConclusionAIMLAM showed promising diagnostic performance in HIV-negative patients. Stratifying patients using lymphocyte cell counting lifted the sensitivity and lowered the cost of LAM, offering a novel diagnostic strategy for tuberculosis in resource-limited settings.